Acidic electrolyzed water more effectively breaks down mature Vibrio parahaemolyticus biofilm than DNase I. (November 2020) - Li, Yufeng; Tan, Ling; Guo, Linxia; Zhang, Ping; Malakar, Pradeep K.; Ahmed, Faraz; Liu, Haiquan; Wang, Jing Jing; Zhao, Yong
Abstract: Extracellular DNA (eDNA) is considered as important determinant in bacterial biofilm formation. This study investigated the effects of DNase I and acidic electrolytic water (AEW) in beaking down mature Vibrio parahaemolyticus biofilms. Changes of key chemical components i.e. eDNA, extracellular proteins, extracellular polysaccharides, extracellular polymeric substances (EPS), and biofilm architecture were primarily used to quantify this effect. A secondary measure was the regulation of genes involved in biofilm formation. DNase I significantly inactivated bacterial cells, degraded eDNA and down-regulated expression of genes involved in biofilm formation ( P < 0.05). However, biofilm architecture was only partially affected. AEW also induced deleterious changes in key chemical components of EPS, and effectively down-regulated genes involved in biofilm formation. In contrast, AEW collapsed the three-dimensional structures of biofilms and prevented the resestablishment of mature biofilms by 12 h when compared to the DNase I. AEW is therefore a more effective agent for controlling Vibrio parahaemolyticus biofilms. Highlights: Degraded eDNA failed to rupture the V. parahaemolyticus mature biofilm. DNase I cannot inhibit the re-formation ability of V. parahaemolyticus biofilm. AEW prolonged the re-formation of V. parahaemolyticus biofilm. AEW was a valid technology to eradicate the mature biofilm of V. parahaemolyticus.